2011
DOI: 10.1002/eji.201041349
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin is a negative regulator of antigen‐activated T cells

Abstract: Adiponectin (APN), a cytokine constitutively produced in fat tissue, has been shown to exert anti-inflammatory effects in various disease models. While the influence of APN on monocytic cells has been extensively studied in vitro, little is known about its role in T cells. In this study, we show that while o10% of human peripheral blood T cells express adiponectin receptors (AdipoRs) on their surface, most T cells store AdipoRs in intracellular compartments. AdipoRs colocalized with immune regulatory molecules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
70
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 94 publications
(78 citation statements)
references
References 34 publications
6
70
1
1
Order By: Relevance
“…Quantitative real-time PCR detected both AdipoR1 and AdipoR2 mRNA in dermal gd-T cells, although AdipoR2 protein expression was below the detection limit by western blot analysis. This result is consistent with the past reports demonstrating discrepancy between mRNA and protein levels of AdipoR2 in leukocytes 41,42 . Control experiments have revealed that AdipoR1 and AdipoR2 mRNA levels are reduced by 465% as evaluated by real-time reverse transcription-PCR analysis (Fig.…”
Section: Resultssupporting
confidence: 94%
“…Quantitative real-time PCR detected both AdipoR1 and AdipoR2 mRNA in dermal gd-T cells, although AdipoR2 protein expression was below the detection limit by western blot analysis. This result is consistent with the past reports demonstrating discrepancy between mRNA and protein levels of AdipoR2 in leukocytes 41,42 . Control experiments have revealed that AdipoR1 and AdipoR2 mRNA levels are reduced by 465% as evaluated by real-time reverse transcription-PCR analysis (Fig.…”
Section: Resultssupporting
confidence: 94%
“…1A, left, and C). In contrast, and as already shown in a recent study [8] less than 10% of CD3 + CD4 + T cells express surface AdipoRs expression (Fig. 1A, right).…”
supporting
confidence: 85%
“…However, the CD56 high subset expresses both receptors intracellularly. Human T cells do store AdipoRs in a similar manner intracellularly within Clathrin-coated vesicles together with CTLA-4 and surface unpregulation is induced by T-cell receptor stimulation [8]. In NK cells we could not induce AdipoRs surface expression by IL-2 or TLR stimulation.…”
mentioning
confidence: 64%
See 2 more Smart Citations